Does palynotaxonomy contribute to the systematics of the genus? The section Multicaulia of the genus Hedysarum (Fabaceae) example in Türkiye - Yilmaz Çitak, Burcu (Acta Botanica Croatica, 2024)
The purpose of the current work was to assess the systematic and taxonomic significance of the pollen morphological characteristics of the Multicaulia section of Hedysarum species found throughout Türkiye using scanning electron microscopy (SEM) and light microscopy (LM) techniques. For this reason, seven different species currently classified in the Multicaulia section were collected from various localities. The pollen grains were nonacetolyzed, prepared and directly measured according to the Wodehouse method. Pollen grains were found to be subprolate in H. nitidum but prolate in others and the exine sculpturing pattern was determined to be microreticulate-perforate in six taxa while only H. varium subsp. syriacum had reticulate-perforate sculpture. The minimum exine thickness was measured at 0.96 μm in H. varium subsp. varium, while among the investigated species, H. nitidum had an exine measurement of 1.38 μm. In this study, multivariate analysis was used to investigate nine qualitative and quantitative features. Data cluster analysis revealed that the pollen characteristics were important in helping to distinguish the different species from one another. The results demonstrated that the genus Hedysarum of the section Multicaulia was divided into two major groups based on variations in pollen dimensions. The usefulness of certain pollen morphological traits was assessed, and the congruency of the palynomorphological investigations was examined. The findings demonstrated the significance of pollen micromorphology in precisely identifying and categorizing the Multicaulia section.